Comparison of 2 modified methods for the active removal of silicone oil with a 23-gauge transconjunctival vitrectomy system. Issue 40 (October 2017) - Ju, Chengqun; Li, Jianqiao; Zhou, Fang; Song, Qi; Wu, Xinyi; Huang, Chao; Li, Shanshan; Wang, Helei
Abstract : Abstract: To report and compare 2 modified approaches for the active removal of silicone oil (ROSO) with a 23-gauge transconjunctival vitrectomy system. This prospective single blinded study was conducted from January 2015 to December 2016. Eighty-nine eyes of 86 patients who underwent silicone oil removal were enrolled. Patients were randomly divided into either group A or B. In group A, the fluid–air exchange tube was connected to a 1 mL syringe with the plunger removed and the tip was dilated with a hemostat so that it fit into the cap of the 23-gauge cannula to form a seal for oil drainage. In group B, the tip of the syringe was closely attached to the cap of the 23-gauge cannula by a tube adaptor, which was salvaged from a used silicone oil inject and aspirate pack and sterilized. Main outcome measures were time required for silicone oil removal, silicone oil residual, intraoperative and postoperative complications including hypotony, bleeding, and retinal redetachment. The mean time required was 6.08 ± 0.31 minutes and 6.11 ± 0.31 minutes for groups A and B, respectively. No silicone oil residual, severe hypotony, recurrence of retinal detachment, or impairment of visual acuity were observed in either group. Conjunctival injection and hyperemia were slightly more severe in group A, but spontaneously resolved in 2 to 3 days. Both methods described in this paper were demonstrated to be safe, effective, and cost-effective for the ROSO. The syringe dilation method caused more severe conjuntival irritation, thus we suggest using the tube adaptor method for hospitals equipped with cold sterilization equipment.